Incorporating multimedia learning into music teacher training program in rural Fujian - Luo, Yan; Liu, Yaoping; Siripala, Wannaporn; Namtubtim, Noppavan; Shen, Yi (Frontiers in Education, 2025)
IntroductionPrevious research has primarily focused on urban settings or general teacher education, often overlooking the unique challenges and opportunities present in rural contexts.MethodsA mixed-method approach was employed, involving 46 music teachers in the teacher training program as the experimental group and 30 music teachers as the control group. The quantitative and qualitative data were collected using close-ended questionnaire to assess teachers’ beliefs about musical skills. Additionally, interviews with 10 teachers were administered after the intervention.ResultsThe findings exhibited that rural music teachers perceived the effectiveness of training program as moderate level. Positive correlation between changes in instructors’ attitudes and beliefs regarding teaching and learning and their views of the teacher training program was also found from the analysis.DiscussionThe study revealed six area of development sural music teachers regarding their technological pedagogical content knowledge (TPACK).